"A Mom First and a Candidate Second": Gender Differences in Candidates' Self-Presentation of Family. Issue 4 (1st October 2016) - Stalsburg, Brittany L.; Kleinberg, Mona S.
Abstract : Parenthood carries different consequences for men and women in politics. While the conventional wisdom is that motherhood is a liability for women candidates and fatherhood an asset for men, recent elections have called this idea into question. Specifically, Sarah Palin's candidacy and her cadre of "Mama Grizzlies" suggest that there may be times when motherhood can be an asset. We analyze how men and women present their families to voters by examining the campaign websites of congressional contenders in 2008 and 2010. The results indicate that despite the proliferation of mother candidates, women still tend to de-emphasize their children compared to their male colleagues, who are more likely to showcase their families, most notably in pictures. Moreover, we find that other factors like parental status, age of children, party, chamber, incumbency, and opponent gender also affect differences in candidates' propensity to use their families in campaigns.